Decomposing the gender wage gap: an analysis of the tourism sector at the European level. - Marfil-Cotilla, Marina; Campos-Soria, Juan Antonio; Ribeiro, Alector; García-Pozo, Alejandro (My University, 2025)
Objective: This paper uses a micro and macro perspectives simultaneously, through a multilevel approach, which may be helpful for understanding how the characteristics of the employees of each country and how the country characteristics can affect the differences at European level in the gender wage gap and its discriminatory component in the tourism sector. Results: A general finding from the analyses indicated that significant variance exists within and among nations in wage structures. The results also show that heterogeneity between countries explained by contextual factors, such as the economic and institutional conditions of the European countries, are key factors for decomposing the gender wage gap in the tourism sector, although, individual heterogeneity due to educational mismatch, labour mobility or occupational segregation, among others, are also relevant.
Keywords: Salarios; Discriminación sexual en el trabajo; Turismo; Gender wage gap; Discriminatory component; Hierarchical linear models; Country heterogeneity; European countries; Tourism